Effect of Wet and Dry Finishing and Polishing Technique on Microhardness and Flexural Strength of Nanocomposite Resins - Amir Ghasemi; Anoosh Mohammadzadeh; Mehdi Molaei; Seyedeh Mahsa Sheikh-; Mandana Karimi (Hindawi Limited, 2023)
Objectives. This in vitro study was aimed to assess the effect of wet and dry finishing and polishing techniques on the flexural strength and microhardness of different commercial nanoparticle contained composite resins. Methods and Materials. The samples were made of Z250 (microhybrid), Z350 XT (nanofilled), and Z550 (nanohybrid) resin composites. Each group was subdivided into 2 subgroups according to polishing protocols. Subgroup 1 for each composite underwent wet polishing, and subgroup 2 was subject to dry polishing technique. Flexural strength and microhardness of the samples were measured at two different times of polishing (T0 and T24). The flexural strength test and microhardness test were measured by a 3-point bending test using a universal testing machine, and a Vickers machine, respectively. Data were analyzed by Kolmogorov-Smirnov, two-way ANOVA, and Tukey HSD tests. Results. ANOVA showed that the type of composite has a significant effect on flexural strength. Two-way ANOVA showed that, at T0, flexural strength of all composites in the dry technique was higher than in the wet technique (p=0.019). At T24, Z350 XT had the lowest, and Z250 had the highest flexural strength in both techniques. The time and technique of polishing were also significantly effective on hardness. At T0, hardness was higher in the wet compared to the dry method (p=0.008). Tukey test showed that, at T24, the hardness of Z350 XT was significantly higher than the other materials in both techniques. Conclusion. Immediate wet finishing and polishing presented lower flexural strength. Delayed dry/wet finishing and polishing significantly enhanced the hardness of the samples.